Central Kenya farmers laud climate-smart Brachiaria grass for increasing income from dairy - International Livestock Research Institute (International Livestock Research Institute, 2021)
Five livestock farmers in Kenya's Kirinyaga County talk about their experiences with using Brachiaria grass as livestock feed. The grass was introduced in the region by the Biosciences eastern and central Africa (BecA)-ILRI Hub’s InnovAfrica project in 2018.